A Learning Experience of the Gender Perspective in English Teaching Contexts (2017)
Eighteen Colombian English teachers participated in a course with an emphasis on gender and foreign language teaching in a Master’s program in Bogotá. This text describes the design, implementation, and the learning in this educational experience. The analysis of the course was based on a view of learning as a process of participation rooted in the praxis of English teachers’ classrooms. This experience reveals that gender is a relevant category in the frame of English language teacher education as it provides teachers with tools from a broader social and educational perspective. This reflection also leads to implications for teachers’ practices with a gender perspective.